The invisible wall: confronting contemporary boundaries in public space - Terblanche, Willem Jacobus (My University, 2022)
Unable to upload abstract
A research report submitted in partial fulfilment of the requirements for the degree of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, 2022